Exploratory Study on the Use of Crushed Cockle Shell as Partial Sand Replacement in Concrete - Khairunisa, Muthusamy; Nurul Nadrah Aqilah, Tukimat (IJRES, 2016)
The increasing demand for natural river sand supply for the use in construction industry along with the issue of environmental problem posed by the dumping of cockle shell, a by-product from cockle business have initiated research towards producing a more environmental friendly concrete. This research explores the potential use of cockle shell as partial sand replacement in concrete production. Cockle shell used in this experimental work were crushed to smaller size almost similar to sand before mixed in concrete. A total of six concrete mixtures were prepared with varying the percentages of cockle shell viz. 0%, 5%, 10%, 15%, 20% and 25%. All the specimens were subjected to continuous water curing. The compressive strength test was at 28 days in accordance to BS EN 12390. Finding shows that integration of suitable content of crushed cockle shell of 10% as partial sand replacement able to enhance the compressive strength of concrete. Adopting crushed cockle shell as partial sand replacement in concrete would reduce natural river sand consumption as well as reducing the amount of cockle shell disposed as waste.